2014
DOI: 10.1177/239700221402800107
|View full text |Cite
|
Sign up to set email alerts
|

Health-Relevant Leadership Behaviour: A Comparison of Leadership Constructs

Abstract: Health-relevant leadership behaviour: A comparison of leadership constructs ** There is empirical evidence that leadership behaviour is related to employee wellbeing. Most studies have analysed the relation between individual leadership constructs and indicators of employee well-being. There has been no systematic comparison of different leadership constructs with respect to their impact on different indicators of employee well-being within the same sample. The aim of our study was therefore to compare differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 76 publications
(107 reference statements)
5
24
0
Order By: Relevance
“…Support for our results also comes from a systematic review of nine systematic reviews by Halter et al (2017), who report managerial style-especially transformational leadership-and supervisory support as among the most relevant factors affecting nurse turnover. Findings from Gregersen et al (2011Gregersen et al ( , 2014 concerning the comparison of different leadership approaches, also lend support to the leadership-related resources we identified and provide insights into the possible relationships between them. Gregersen et al (2011) literature review of employees in different industries linked leadership to employee well-being and found that social support was strongly associated with employee health, as were transformational leadership and employeeoriented leadership.…”
Section: Work-life Interferencesupporting
confidence: 56%
See 1 more Smart Citation
“…Support for our results also comes from a systematic review of nine systematic reviews by Halter et al (2017), who report managerial style-especially transformational leadership-and supervisory support as among the most relevant factors affecting nurse turnover. Findings from Gregersen et al (2011Gregersen et al ( , 2014 concerning the comparison of different leadership approaches, also lend support to the leadership-related resources we identified and provide insights into the possible relationships between them. Gregersen et al (2011) literature review of employees in different industries linked leadership to employee well-being and found that social support was strongly associated with employee health, as were transformational leadership and employeeoriented leadership.…”
Section: Work-life Interferencesupporting
confidence: 56%
“…Gregersen et al (2011) literature review of employees in different industries linked leadership to employee well-being and found that social support was strongly associated with employee health, as were transformational leadership and employeeoriented leadership. Based on a subsequent empirical study with more than 1,000 nursing home employees in Germany (Gregersen et al, 2014) they propose that an important shared element between these different health-promoting leadership approaches may lie in trustful inter-individual relationships between the supervisor and the employee. This supports an individualized approach to interacting with each employee, rather than adhering strictly to a specific leadership style.…”
Section: Work-life Interferencementioning
confidence: 99%
“…The extant literature suggests that managers' leadership skills and behavior influence their subordinates' well-being or health through their impact on creating working conditions and the possibility to provide their subordinates with health-promoting resources [5,6,9]. However, many organizations seem to neglect the contribution of the managers to employees' stress, and stress-related illnesses [1].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a manager may become a model of health-promoting behavior giving example of his or her own strategies or just attitude to health protection [8]. The research revealed that superior-subordinate exchange [9] understood as a unique relationship that a manager has with each of subordinates, influences employees' health and well-being to a greatest extent, as compared to other acknowledged leadership behavior. The research results revealed that this relationship determined not only the general health but also job satisfaction, emotional exhaustion or work-related strain.…”
Section: Individual Level (Superior-subordinate Relationship)mentioning
confidence: 99%
“…Dimoff et al (2016) found that a short training session for supervisors and managers increased their knowledge of and attitudes towards employee well-being, their self-efficacy, and intent to promote well-being at work. Gregersen et al (2014), in a sample of 1045 German healthcare workers, compared various leadership constructs as predictors of employee positive well-being (e.g., job satisfaction and general health) and negative well-being (e.g., emotional exhaustion, depersonalization, psychological strain as measured by an irritation scale). Leadership constructs included transformational, transactional, leader-member exchange, consideration and initiating structure.…”
Section: Leadership and Employee Well-beingmentioning
confidence: 99%